An observational study on forest landscape conservation in Malaysia via the establishment of Forestry Educational Centres - Hussein, Mohd Kher; Mohd Yusof, Mohd Johari; Jaafar, Nor Syuriaty (Universiti Sains Malaysia Press, 2020)
The establishment of the forestry educational centre is a good effort made to protect and conserve the forest as well as assisting the public in understanding the landscape changes and sensitivity towards its sustainability. However, there are lacks of consciousness and obligation of the important of landscape conservation in the context of development planning that causes the problem of effective implementation of a conservation strategy exists. Therefore, this paper aims to discuss forest landscapes conservation, particularly in Malaysia with the objectives of to analyse the current landscape features of selected forestry educational centres and to increase awareness among the stakeholders on the importance of conserving and preserving forest landscape towards its sustainability. The study was conducted using two methods specifically via a case study where the Sultan Idris Shah Forestry Education Center (SISFEC) was selected and field observations were conducted to analyse the existing physical condition of the study site. Findings have indicated that SISFEC has successfully conserved the existing landscapes and delivered awareness and knowledge on forest conservation and preservation to the public through several activities such as forestry camps, nature walks, and environmental education programmes. On the other hand, the findings also suggested that the forestry management should give higher priority in maintaining the manmade landscape image of the forest and plan their activities well through good monitoring and efficient management planning which will ensure the site's sustainability in future.